Upaya Meningkatkan Hasil Belajar Ekonomi Dengan Menggunakan Metode Problem Solving pada Peserta Didik Kelas XI IPA di SMA muhammadiyah Kasongan - Muhammad Farmo; Muhamad Ramli (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to determine the Activity and to know the increase in economic learning outcomes after using the Problem Solving method. This research is a classroom action research. The subjects of this study were students of the Kasongan Muhammadiyah High School class XI consisting of 17 students. Analysis of the data used in this study is qualitative data and quantitative data. Based on the research obtained: (1) Learning activities of students become good. Cycle I had an average score of 2.8 with quite good criteria then in cycle II the average score obtained by students was 3.8 with good criteria. (2) There is an increase in student learning outcomes. In the pre-action process when the pre-test obtained an average value of 67 with classical completeness of 35% with criteria not reached, Cycle I obtained an average value of 81 with classical completeness of 76.47% with criteria not achieved and in post-test cycle II obtained grades an average of 89 with 100% classical completeness with the criteria reached.